Ketika Bermedia Sosial Mengganggu Komunikasi Interpersonal: Studi Korelasi pada Karyawan Generasi Y - Dhevinda Maudhy Dwi Poetry; Nuri Sadida (Jurnal Ilmiah Psikologi MIND SET, 2019)
In the work environment, generation Y shows proficiency in the use of technology, including social media. The Y generation spent more hours per day accessing social media compared to previous generation. Frequent use of social media can result in the loss of interaction ability directly. Present phenomenon shows that generation Y has difficulty communicating and inappropriate approach in communication. This study aims to determine the relationship between the frequency of using social media and interpersonal communication in Y generation’s employees. Sample in this study were 131 employees with aged 22-38 years who works in DKI Jakarta and have more than one social media. The instruments that were used are The Media and Technology Usage and Attitude Scale (Rosen, 2013) and Interpersonal Communication Inventory (Graham, 1998) which have been adapted. The result of this study indicated that there was negative significant relationship between frequency of social media usage and dimension awareness of others from interpersonal communication. However, in other dimension indicated that there was no correlation between frequency of social media usage and both of dimension, which are awareness of self & self disclosure and coping with feelings & differences.